Understanding Poverty Dynamics in Indonesia: The Role Economic Growth, Income Distribution, and Human Development - Pardita, Dewa Putu Yudi; Arjawa, I Gde Wedana; Paramita, Anak Agung Gde Krisna; Setena, I Made (Universitas Pasundan, 2024)
This study aims to analyze the influence of economic growth, income distribution, and the Human Development Index (HDI) on poverty in Indonesia, both partially and simultaneously. The data used in this research is secondary data, comprising a total of 680 observations from 34 provinces in Indonesia over the period 2018-2022. The data analysis technique employed in this study is panel data regression. The results of this study indicate that, partially, economic growth and income distribution have significant effects on the poverty level in Indonesia. Meanwhile, the Human Development Index (HDI) does not have a significant impact on poverty levels in Indonesia. Simultaneously, economic growth, income distribution, and the Human Development Index (HDI) together have a significant effect on poverty in Indonesia. Based on the results of this study, it is recommended that the government implement effective policies through progressive taxation, direct cash transfers to poor families, and social protection programs targeted specifically at those below the poverty line. Additionally, investment in education must be increased to ensure broader access and better-quality education for all segments of society.